Immunomodulatory Effects of Heme Oxygenase-1 in Kidney Disease - Li, Yunlong; Ma, Kuai; Han, Zhongyu; Chi, Mingxuan; Sai, Xiyalatu; Zhu, Ping; Ding, Zhaolun; Song, Linjiang; Liu, Chi (Frontiers in Medicine, 2021)
Kidney disease is a general term for heterogeneous damage that affects the function and the structure of the kidneys. The rising incidence of kidney diseases represents a considerable burden on the healthcare system, so the development of new drugs and the identification of novel therapeutic targets are urgently needed. The pathophysiology of kidney diseases is complex and involves multiple processes, including inflammation, autophagy, cell-cycle progression, and oxidative stress. Heme oxygenase-1 (HO-1), an enzyme involved in the process of heme degradation, has attracted widespread attention in recent years due to its cytoprotective properties. As an enzyme with known anti-oxidative functions, HO-1 plays an indispensable role in the regulation of oxidative stress and is involved in the pathogenesis of several kidney diseases. Moreover, current studies have revealed that HO-1 can affect cell proliferation, cell maturation, and other metabolic processes, thereby altering the function of immune cells. Many strategies, such as the administration of HO-1-overexpressing macrophages, use of phytochemicals, and carbon monoxide-based therapies, have been developed to target HO-1 in a variety of nephropathological animal models, indicating that HO-1 is a promising protein for the treatment of kidney diseases. Here, we briefly review the effects of HO-1 induction on specific immune cell populations with the aim of exploring the potential therapeutic roles of HO-1 and designing HO-1-based therapeutic strategies for the treatment of kidney diseases.